A proposal for the use of Core and Buffer Zones to protect the heritage of the Cyrenean landscapes. (4th September 2019) - Menozzi, Oliva; Cherstich, Luca; Di Valerio, Eugenio; Di Antonio, Maria Giorgia; Abdalrahim Shariff Saad, A.
Abstract: The ancient landscapes surrounding Cyrene, which have been incredibly well preserved for centuries, have suffered more destructions in the past 7 or 8 years than in the whole of the last millennium. Urban encroachment, strong demographic pressure, unsustainable exploitation of resources and unplanned growth of infrastructures and services are threatening the archaeological heritage of this splendid site. The Department of Antiquities (DoA) has always struggled against these phenomena, but today the destructions are so great that the DoA is often powerless to act. This paper continues previous works on the damage to the Cyrenean necropoleis after 2011(Abdulkariem and Bennett, 2014; Al Raeid et al. 2016; Menozzi, Di Valerio et al. 2017; Menozzi, Tamburrino et al. 2017) and proposes strategies to help, on the basis of a preliminary report organised by the Mission of the University of Chieti in collaboration with the Departments of Antiquities of Cyrene and Tripoli, as requested by UNESCO. This preliminary step towards further improvements and needs to be discussed with other institutions and missions. The first part presents a proposal for controlling the core and buffer zones around Cyrene; the second part is an update on the recent damages to the necropoleis. Abstract : إن المشاهد الأثرية المحيطة بقوريني (شحات) التي تم الحفاظ عليها جيداً لعدة قرون، قد تعرضت في السنوات السبع أو الثماني الماضية لدرجة من التدمير تمثل أكثر مما تعرضت له خلال الألفية الماضية بأسرها. إن التعدي الحضري والضغط الديموغرافي القوي، والاستغلال الغير مستدام للموارد و النمو الغير مخطط له للبنية التحتية و الخدمات، جميعها تهدد التراث الأثري لهذا الموقع الرائع. لقد صارعت مصلحة الأثار دائماً هذه الظواهر، ولكن اليوم أصبح التدمير كبير جداً لدرجة أن مصلحة الأثار غالباً ما تكون عاجزة عن التصرف. هذه الورقة هي استمرارية للأعمال السابقة بشأن الأضرار التي لحقت بمقبرة قوريني بعد عام 2011 (عبد الكريم و بينيت، 2014؛ الرعيض وآخرون 2016؛ مينوزي و دي فاليريو وآخرون 2017؛ مينوزي و تامبورينو وآخرون (2017 حيث تقترح استراتيجيات للمساعدة، على أساس تقرير أولي أعدته بعثة جامعة كييتي بالتعاون مع مصلحة الأثار بكل من قوريني و طرابلس، و بناءً على طلب من اليونسكو. هذه الخطوة الأولية نحو مزيد من التحسينات تحتاج إلى مناقشة مع المؤسسات والبعثات الأخرى. يقدم الجزء الأول اقتراحاً للسيطرة على المناطق الأساسية والعازلة حول قوريني؛ و الجزء الثاني هو تحديث يتناول الأضرار الأخيرة التي لحقت بالمقبرة.